The Key Sectors in CO2 Emission in Indonesia: Input Output Analysis - Imansyah, M. Handri; Putranti, Titi Muswati; Affandi, Dean Yuliandri; Khafian, Nidaan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
This research is intended to identify changes of key sectors in CO2 emission over the period of 1990-1995. This research uses input-output method for mapping of the biggest polluting industry. By identifying the highest output multiplier, CO2 emission and change of final demand can be known from each of sectors. The research results show that there is emission reduction in the fifteen key sectors over 1990-1995, but there is no significant change in the five key sectors that are still the highest polluters.